AN ANALYSIS OF CODE MIXING USED BY EFL STUDENTS IN THE CLASSROOM PRESENTATION - Fadliyah, Riskatul; Dollah, Syarifuddin; Muhayyang, Maemuna (PT ARRUS Intelektual Indonesia, 2023)
This descriptive qualitative research aims to have a descriptive account of the types of code mixing used by the EFL students in the classroom presentation for the English course provided. The researchers conducted this research at the English Education Faculty of Institut Parahikma Indonesia, Gowa (IPI Gowa) purposely taking 1 lecturer teaching the English course and 1 class of the fourth semester students consisting of 10 students having a classroom presentation as one of the learning activities designed. It employed a classroom observation and open interview to collect the data in which their results were classified based on Musyken’s theory (2000) and analyzed using the theory of Miles, Hubberman, and Saldana (2020) coming with three stages of the interactive model data analysis, namely data condensation, data display, and conclusion drawing or verification. The result of data analysis showed that the code-mixing types utilized by the students when doing the presentation were three, that is (1) insertion (word) taking the most dominant type used with 27 extracts, (2) alternation (clause) taking more dominant type used with 15 extracts, and (3) congruent lexicalization (dialect) taking the least with 12 extracts in the classroom presentation. These findings simply means that the use of code mixing becomes the students’ communicative strategy channeling the presenters and the audiences’ ways of understanding the points of their discussion during the classroom presentation.